Conversation teasers in education : the heart of education - Erguiza, Narciso Jr.; Tee, Maria Virlinda (Quezon City, Philippines : Phoenix Publishing House, Inc., 2020)
This book then looks at education as a major game changer and therefore looks at education from a non-traditional perspective.
Dedication -- Prologue -- Introduction -- Conversation Teasers in Education -- State of Education in the country 2020 -- Why the Philippines ranks last in Mathematics, Science and Reading -- Teaching as a Vocation -- Open High School/University or Distance Learning -- Educational Game Changer -- Language and Significant Persons -- Teaching Mathematics in Grade 3 -- Why I hated Mathematics and Science -- All things to everyone -- An Influential Teacher -- Close All Schools: Start Educating -- Parents as Primary Educators -- Online Learning -- Innovative Education -- Disruptive Education -- How Subversive are teachers in their teaching -- Traditional Education -- Stages of Moral Development and Education -- The President as an Education Leader -- Science in Kindergarten -- A Nation of Non-Readers -- Competence and Integrity -- Educational Radio and Television -- A Sample presentation for Grade 3, Health Nutrition, Exercise, Prevention and cure -- A day in the life of a teacher -- Institutions of public trust -- Special Kids = Special Teachers -- Selective Listening = Learning -- Is teacher's Salary Enough? -- Spirit of Zeal -- Passion and Compassion -- Education in Legislative Decision Making -- Reading: The Key to Success -- Subversive Education -- Teaching Research in Kindergarten -- A Community Talents -- Future of Supervised Schools -- A System of Leadership and Management -- ARETE -- You are De La Salle Today -- The Intellectually Gifted Child -- Anti-Bullying: A Violence Prevention Education -- Culturally-Responsive Teaching in a Nutshell -- Values-Based Education in Capsule -- The Heart, Head and Hand of Instructional Leaders -- A Test of Competence -- Professional Teacher's Global Competence -- The Medical Doctor Professional Competence -- The Certified Public Accountant Professional Competence -- The Doctor of Dental Medicine Professional Competence -- Indigenous People's Education -- Let's Go GREEN ! Save Mother Earth -- Peace Education -- Gender Education -- Education for Social Justice and Human Rights -- Intercultural Education -- Mainstream-Inclusive Education -- Mother Tongue Based- Multi-Lingual Education -- Teaching for Meaning and Mastery -- Brain-Based Learning -- Multi-Grade Teaching -- How Humor-Filled is your Class Session -- Education for change -- Graphic Organizers: Metacognitive Thinking Technology -- Flipped Classroom -- Creative and Imaginative Teaching and Learning Experience -- Critical Thinking Strategies -- The Rubicon Model for Students Engagement and Motivation -- The Generation Cohorts of Millenial Students.
Keywords: EDUCATION